IMPROVING READING SKILL THROUGH LOOK AND SAY METHOD - Sitti Aisyah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
This Research aimed to find the students’ reading skill achievement after teaching them through look and say method. The questions posed in this research are “how is the first-year students’ ability of SMAN 1 Tanralili Maros in reading English?” and “How is the improvement of the students’ reading skill through look and say method?”. The method applied in this study was pre-experimental which applied pre-test and post-test. The population of this research was the first-year students of SMAN 1 Tanralili Maros. The writer applied the purposive sampling technique, so the number of the sample was 30 students. The research of data analysis indicated that there some a significant increase in the students’ achievement in reading skill after teaching them through look and say method. It was proved by the result of the statistical analysis of the level significant 0,05 with the degree of freedom (df = n-1 = 29) indicated that t-test value was 10,57. While t-table was 2,120 where 10,57 > 2,045.Based on the fact the writer concluded that the reading skill of the first-year students of SMAN 1 Tanralili Maros that had got treatment by teaching them through look and say was significantly different before they got treatment.